Investment Feasibility Study for the Development of Salak Chips Products at PT Spirit Jaya Snack and Coffee, Malang City, East Java - Warter Agustim; Stefania Maha; Nur Ida Iriani (International Journal of Management and Business, 2026)
The purpose of this research is to evaluate the feasibility of investment in new product development at PT. Spirit Jaya Snack and Coffee. The research method used is a quantitative method, using data collection techniques through interviews, observation and secondary data analysis. The results of the study show that the development of new products at PT. Spirit Jaya Snack and Coffee is worth doing, with a Net Present Value (NPV) value of Rp. 1,262,301,332, Payback period (PP) of 11 Months and Internal Rate of Return (IRR) of 17.39%. However, the company needs to consider several factors, such as market risk, operational risk, and financial risk to ensure the successful development of new products for salak chips.